Al-Khilaf ‘inda Daulah Qatr wa Mitsl al-Jins fi Ka’si al-'Alam 2022: Tahlil al-Khitab al-Naqd li Ruth Wodak - Az Zahro, Fatimah; Mardiah, Zaqiatul (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This research aims to reveal the alignment of the BBC news portal in the conflict that occurred at the 2022 World Cup. From October to the end of November 2022, the BBC will carry headlines about the Qatar-LGBTQ community-FIFA triangular conflict. This BBC news is interesting to examine critically through the lens of Ruth Wodak (2001), namely historical and discursive strategies. This study uses the Wodak paradigm to criticize the BBC news text about the conflict to reveal the media's ideology and partiality in this case. Wodak always involves historical aspects of discourse content because news texts never stand alone but are related to events in the past. The discursive aspect becomes a tool to frame how news is presented using language as a social practice. The research results state that the BBC is a pro-LGBTQ community. This inclination can be seen from the BBC's language presentation, word choice, and the language structure used by the BBC in presenting news. The BBC is also very skilled at inserting rejection of Qatar's principles through human rights presentations.